An Approach for Sustaining Biodiversity in India - Mehrotra, A.; Kushalapa, K. A. (Indian Forester, 1994)
The global concern for preserving the Biodiversity for immediate as well as future use has gained momentum after the historic Rio Convention in 1972. India as one of the signatories of this Convention has made great strides for the conservation of Biodiversity. Essentially, any sustainable use and wise management of Biodiversity requires assessments of diversity, legal enactments and division of work at National and State levels. The present paper focuses the attention on these issues and suggests an approach to find the solution.